2021
DOI: 10.3390/fluids6020067
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Forces Impacting Cleavage of Von Willebrand Factor in Laminar and Turbulent Blood Flow

Abstract: Von Willebrand factor (VWF) is a large multimeric hemostatic protein. VWF is critical in arresting platelets in regions of high shear stress found in blood circulation. Excessive cleavage of VWF that leads to reduced VWF multimer size in plasma can cause acquired von Willebrand syndrome, which is a bleeding disorder found in some heart valve diseases and in patients receiving mechanical circulatory support. It has been proposed that hemodynamics (blood flow) found in these environments ultimately leads to VWF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…While the shape of vWF is dynamic and dependent on the type of flow, in general the vWF multimers have overall compact, bird’s nest shape. The behavior of the vWF as a sphere has been adopted by others, e.g., Gogia et al 29 and Sharifi and Bark 74 . It was treated implicitly as a sphere in Pushin et al 75 , since the forces acting on the vWF were assumed there-in to be found as stress multiplied by the area of a circle.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the shape of vWF is dynamic and dependent on the type of flow, in general the vWF multimers have overall compact, bird’s nest shape. The behavior of the vWF as a sphere has been adopted by others, e.g., Gogia et al 29 and Sharifi and Bark 74 . It was treated implicitly as a sphere in Pushin et al 75 , since the forces acting on the vWF were assumed there-in to be found as stress multiplied by the area of a circle.…”
Section: Methodsmentioning
confidence: 99%
“…When the hydrodynamic and mechanical stresses are low, the multimers attain a compact (collapsed) conformation because of effective interdomain attractions 76 . Above a critical shear stress, the vWF free in flow would elongate and tumble, and it would extend in elongational flow 41 , 74 . Since such changes were not modeled in this study, the hydrodynamic radius was used for computations.…”
Section: Methodsmentioning
confidence: 99%
“…Bortot et al have shown that the cleavage of vWF as facilitated by the turbulent flow conditions leads to the functional deficiency of vWF [ 17 ]. Sharifi et al adopted the scission theory for polymers on biological multimers providing an understanding of flows producing strong extensional forces on vWF and resulting to cleavage, especially in turbulent flow [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of a particle diameter in the Stokes-Einstein equation was justified by the assumption that the most important contributions to the motion of the vWF were convection and Brownian motion, while drag effects were not important. Prior researchers have also assumed that the vWF can be treated as a sphere [ 18 , 40 ]. Others have implied in their analysis that the vWF is spherical, for example Pushin et al [ 41 ] assumed that the forces acting on the vWF could be calculated as stress multiplied by the area of a circle (i.e., the circle is the projected area of a sphere on the stress plain).…”
Section: Introductionmentioning
confidence: 99%
“…20,21 However, these rotary pump designs can lead to very high pathological shear stress, which is known to cause platelet activation, hemolysis, and acquired von Willebrand syndrome, among other issues linked to previously stated adverse events. 12,[22][23][24] Efforts toward smaller devices with the same flow output are likely to lead to the same high shear problems.…”
Section: Introductionmentioning
confidence: 99%